1998
DOI: 10.2307/749861
|View full text |Cite
|
Sign up to set email alerts
|

The Empty Number Line in Dutch Second Grades: Realistic versus Gradual Program Design

Abstract: In this study we compare 2 experimental programs for teaching mental addition and subtraction in the Dutch 2nd grade (N = 275). The goal of both programs is greater flexibility in mental arithmetic through use of the empty number line as a new mental model. The programs differ in instructional design to enable comparison of 2 contrasting instructional concepts. The Realistic Program Design (RPD) stimulates flexible use of solution procedures from the beginning by using realistic context problems. The Gradual P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 13 publications
4
81
1
1
Order By: Relevance
“…Although researchers do not always use the same wording-for example, other expressions can be found in Klein, Beishuizen, & Treffers (1998) and Torbeyns, De Smedt et al, (2009)-there is broad agreement about the general meaning of these strategies. To use a splitting strategy, the subtraction problem is solved by decimally splitting both the minuend and the subtrahend and processing the tens and the ones separately (e.g., 54 − 31 is calculated as 50 − 30 and 4 − 1, with 23 as the final answer).…”
Section: Strategies and Procedures For Solving Addition And Subtractimentioning
confidence: 99%
See 3 more Smart Citations
“…Although researchers do not always use the same wording-for example, other expressions can be found in Klein, Beishuizen, & Treffers (1998) and Torbeyns, De Smedt et al, (2009)-there is broad agreement about the general meaning of these strategies. To use a splitting strategy, the subtraction problem is solved by decimally splitting both the minuend and the subtrahend and processing the tens and the ones separately (e.g., 54 − 31 is calculated as 50 − 30 and 4 − 1, with 23 as the final answer).…”
Section: Strategies and Procedures For Solving Addition And Subtractimentioning
confidence: 99%
“…To contribute to this broad understanding of subtraction, students should be given more than just bare number problems. Several studies (Klein et al, 1998;Torbeyns et al, 2009b;Blöte et al, 2001;Van den Heuvel-Panhuizen, 1996) revealed that bare number problems hardly evoke the use of IA, which can be explained by the presence of the minus sign that emphasizes the "taking-away" action (Van den Heuvel-Panhuizen, 1996). Context problems, on the contrary, lack this operation symbol and therefore open up both interpretations of subtraction (Van den Heuvel-Panhuizen, 2005).…”
Section: Influence Of Problem Formatmentioning
confidence: 99%
See 2 more Smart Citations
“…So as the Realistic Mathematics Education (RME) literature suggests perhaps a better way to begin might be by modelling a numberline-based method of counting-on that keeps the first number "whole" as this method does transfer to subtraction. In RME this method is known as the "N10" procedure, and it is contrasted from the "1010" procedure which splits both numbers to be operated upon (Klein, Beishuizen & Treffers, 1998). We discuss this further below when reviewing related literature.…”
Section: Vignettes From the Eastern Cape And Gautengmentioning
confidence: 99%